Differential-Associative Processing for Learning Concepts in Compared to Other Strategies Even after the Influences of Pre-Testing Reviews and Delays - Hannon, Brenda (An Overview of Literature, Language and Education Research Vol. 5, 2024)
Recent studies show that a strategy called differential-associative processing is effective for learning related concepts. However, little research has examined the influences of short delays on knowledge that is acquired by using differential-associative processing. Thus, it is unclear whether differential-associative processing’s mnemonic value extends beyond immediate testing. The goal of the present study is to extend our knowledge of differential-associative processing by assessing the duration of knowledge that is acquired by using differential-associative processing, as well as the efficacy of differential-associative processing after a 10-minute pre-testing review. The results revealed that a condition that used differential-associative processing for learning concepts resulted in better learning compared to conditions where students employed a strategy of their own choice. The results also revealed that a 10-minute pre-testing review had a positive additive influence on differential-associative processing. Finally, although the knowledge acquired from using differential-associative processing declined as the delay between learning and testing increased, this decline was equivalent to the decline observed in all learning conditions. It is concluded that differential-associate processing is an excellent strategy for learning pairs of similar concepts and that future research should seek to apply this strategy to other types of material, such as books or vocabulary words.